Overlap coefficients based on Kullback-Leibler divergence: Exponential populations case - Dhaker, Hamza; Ngom, Papa; Mbodj, Malick (International Journal of Applied Mathematical Research, 2017)
This article is devoted to the study of overlap measures of densities of two exponential populations. Various Overlapping Coefficients,Â namely: Matusitaâ€™s measure Ï, Morisitaâ€™s measure Î» and Weitzmanâ€™s measure âˆ†. A new overlap measure Î› based on Kullback-LeiblerÂ measure is proposed. The invariance property and a method of statistical inference of these coefficients also are presented. Taylor seriesÂ approximation are used to construct confidence intervals for the overlap measures. The bias and mean square error properties of theÂ estimators are studied through a simulation study.